PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 94 PEKANBARU - Wulandari, Yuni Ariani; Alpusari, Mahmud; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is motivated by the low learning result for third grader students of Primary School 94 Pekanbaru on science. It can be seen from the Minimum Criteria of Mastery Learning is 75 and there were 6 out of 31 students who passed the Minimum Criteria of Mastery Learning (19.36%) and those who did not reach the Minimum Criteria of Mastery Learning were 25 students (80.64%) with average score is 60.96. This study aims to improve the learning result of science through inquiry learning model for third grader students of Primary School 94 Pekanbaru. This type of research is classroom action research. Moreover, the data collection techniques are learning result test and observation sheet. The test is used to collect the data such as student learning result and the observation sheet is used to collect data on teacher and student activities. The pre-test that has passed score is 19.36%. Meanwhile, the post-test in the first cycle improves about 45.16% and the improvement in the second cycle is 83.87%. Based on the results of the study, it can be concluded that the implementation of inquiry learning model can improve science learning result of third grader students at Primary School 94 Pekanbaru.Keywords: Inquiry Learning Model, Science Learning Result